EFFICACY OF FUNGICIDES AGAINST PHYTOPHTHORA INFESTANS AT ELEVATED TEMPERATURE IN THE ERA OF GLOBAL CLIMATE CHANGE - Yadav, Saurabh; Lal, Mehi; Singh, BP; Kaushik, SK; Sharma, Sanjeev (Potato Journal, 2016)
Late blight caused by Phytophthora infestans (Mont.) de Bary still remains the most important threat to potato cultivation even after more than one and half century of its first appearance. Although, the best strategies to combat this menace is to breed for host resistance yet, the experience so far has been that resistance in potato varieties break down within a decade of their deployment. Hence, the only alternative left is use of fungicides to control the disease to supplement host resistance. This scenario has been further complicated due to the global climate change resulting into elevated temperature and CO2 levels and efficacy of fungicides may also be affected. In the present study an attempts was made to study the efficacy of fungicides (dimethomorph, cymoxanil based, metalxayl based and mancozeb) at elevated temperatures in growth chamber to simulate the effect of climate change. The effects of these fungicides on the lesion growth and sporulation were measured at 1, 7 and 14 days after spray application. Result revealed that up to 7 days all the tested fungicides were effective. However, no fungicide except dimethomorph based could check the infection at 300c after 14 days of spray application. Fungicides cymoxanil based, mancozeb and metalaxyl based showed 50.17%, 47.43% and 48.23% degradation respectively. Our study clearly established elevated temperature as a key factor for reducing the efficacy of fungicides that becomes the most important cause of concern for pathologists and needs immediate interventions to redraw the late blight management strategies for potato crop.